2017
DOI: 10.1007/s11936-017-0549-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): A Lipoprotein Whose Time Has Come

Abstract: Cardiovascular disease is a leading cause of morbidity and mortality in the USA and around the world. While we are now able to achieve significant low-density lipoprotein cholesterol (LDL-C) lowering with current therapies, many patients remain at risk for cardiovascular disease (CVD). Elevated lipoprotein(a) [Lp(a)] has been shown to be an independent risk factor for CVD and accounts for some of the residual CVD risk after LDL-C lowering in several large clinical trials. Moreover, there is now strong evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…ere are two categories of immunological assays used to measure Lp(a) levels. e first category of immunological assays is "isoform-dependent, " representing the entire protein mass of Lp(a), reported in milligrams per (deciliter/liter) [183]. e molecular mass of the apo(a) protein mainly depends on the number of K IV motif repeats, with an extremely wide range of 200-800 kilodaltons [39].…”
Section: Lp(a) Measurementmentioning
confidence: 99%
“…ere are two categories of immunological assays used to measure Lp(a) levels. e first category of immunological assays is "isoform-dependent, " representing the entire protein mass of Lp(a), reported in milligrams per (deciliter/liter) [183]. e molecular mass of the apo(a) protein mainly depends on the number of K IV motif repeats, with an extremely wide range of 200-800 kilodaltons [39].…”
Section: Lp(a) Measurementmentioning
confidence: 99%
“…Thus, to our knowledge, we are the first to demonstrate an independent association between Lp(a) concentration and ARAS in a hypertensive low LDL-c population. Pathophysiologically, the mechanisms by which Lp(a) increases CVD risk are driven by proatherogenic and prothrombotic states, including endothelial disorder, smooth muscle proliferation, foam cell formation, and local coagulation disturbances [13]. Molecularly, Lp(a) is similar to LDL-c, as it is a particle covalently bound by apoB and apo(a), which carries pathogenic LDL-c and leads to atherosclerosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent ESC article, lipoprotein(a) [Lp(a)] was highlighted as a CVD risk estimator [8]. Studies from the past few decades have revealed that populations with well-regulated LDL-c levels still had a considerably high residual cardiovascular risk, and that Lp(a) is responsible for this phenomena [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This cross-sectional study indicated that, in a hypertensive Chinese population with low levels of LDL-c, Lp(a) was identified as a significant residual risk factor for ARAS. Pathophysiologically, the mechanisms by which Lp(a) increases CVD risk are driven by proatherogenic and prothrombotic states, including endothelial disorder, smooth muscle proliferation, foam cell formation, and local coagulation disturbances [13]. Molecularly, Lp(a) is similar to LDL-c, as it is a particle covalently bound by apoB and apo(a), which carries pathogenic LDL-c and leads to atherosclerosis [31].…”
Section: Discussionmentioning
confidence: 99%